Implementasi Restorative Justice pada Kasus Guru Honorer Supriyani - Hamirul; Nanang Al Hidayat; Syahwami (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
In Supriyani's case which is currently viral, researchers want to know why the implementation of Restorative justice as mandated in regulations cannot run well and efficiently. Normative juridical research is a method used in research where library research. Restorative justice is a way of resolving cases through a legal process outside of court which aims to achieve justice which emphasizes restoration of the condition of the perpetrator and the victim. The mediation carried out did not reach an agreement between the reporting party and the reported party due to a request for peace money amounting to IDR 50,000,000, which resulted in when the mediation failed and then teacher Supriyani was detained for 1 week and because this case went viral and became public attention, teacher Supriayani was finally suspended temporarily until she waited for the next stage.